Mitigating the Transmission of COVID-19 with the Appropriate Usage of Personal Protective Protocols and Equipment in Breast Imaging and Intervention. Issue 2 (22nd January 2021) - Moseley, Tanya W; Conners, Amy L; He, Hongying; Barth, Jean E; Lightfoote, Johnson B; Parikh, Jay R; Whitman, Gary J
Abstract: The integration of personal protective equipment (PPE) and procedures into breast imaging and intervention practices will mitigate the risk of transmission of COVID-19 during the pandemic. Although supply chain shortages have improved, understanding the proper use of PPE and protocols to mitigate overconsumption are important to ensure efficacious utilization of PPE. Protocols and best practices are reviewed, and guidelines and resource materials are referenced in order to support breast imaging healthcare professionals. Graphical Abstract: